Получение композитов В4С – ТiВ2 с повышенной вязкостью разрушения - Ивженко, В.В.; Кайдаш, О.Н.; Сарнавская, Г.Ф.; Попов, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The kinetic regularity of uniaxial hot pressing in the system B4C–TiH2 has been determined. The structure consists of the matrix phase of В4С and the intergranular phase of titanium diboride (carboboride) with low mutual solubility. The physical-mechanical properties of materials in the dependence on the composition have been studied. With increase of titanium hydride content up to 9 % (by volume) the hardness is decreased on 16 %, the bending strength is’t influenced ~500 MPа, the fracture strength is enhanced on 60 %.